Lactobacillus johnsonii La1 antagonizes Giardia intestinalis in vivo - Humen, Martín Andrés (2005)
This study describes the in vivo activity of Lactobacillus johnsonii La1 (NCC533) in Giardia intestinalis-infected gerbils (Meriones unguiculatus). Daily administration of lactobacilli in the drinking water from 7 days before inoculation with Giardia trophozoites efficiently prevented G. intestinalis strain WB clone C6 from infecting gerbils. More specifically, shedding of fecal Giardia antigens (GSA65 protein) was diminished in the La1-treated group, and resolution of infection was observed by 21 days postinoculation. Histology and analysis of enzymatic markers of microvillus membrane integrity revealed that probiotic administration also protected against parasite-induced mucosal damage. In addition, a cellular response to Giardia antigens was stimulated in spleen cells from La1-treated gerbils. Results show for the first time the antigiardial effect of probiotic lactobacilli in vivo and provide further insight into the antagonistic properties of lactic acid bacteria against protozoa involved in intestinal infections.